Neurological and functional recovery in multiple injured patients with paraplegia: outcome after 1 year - Putz, Cornelia; Schuld, Christian; Akbar, Michael; Grieser, Thomas; Wiedenhöfer, Bernd; Fürstenberg, Carl Hans; Gerner, Hans-Jürgen; Rupp, Rüdiger (The journal of trauma, 2011)
BACKGROUND: Injuries of thoracic vertebrae in multiple trauma patients are often accompanied by severe thoracic injuries and sensorimotor deficits. However, until now, it is not clear whether and how the severity of trauma influences the neurologic and functional outcome in paraplegic patients during the first year after the trauma. The aim of the study was to compare two cohorts of multiple injured paraplegic patients with and without conversion in the American Spinal Injury Association Impairment Scale (AIS) with regard to the severity of spinal trauma, the severity of thorax trauma, the type of fracture, and the functional outcome 1 year after the date of injury. - METHODS: Twenty-one traumatic paraplegic patients (neurologic level T1-T12) were included in the study based on a retrospective analysis of the Heidelberg European Multicenter Study about Spinal Cord Injury database (www.emsci.org) from 2002 to 2007. In all patients, the Polytraumaschluessel (PTS), the AO classification, the AIS, and the Spinal Cord Independence Measure were collected. Patients with no change in the AIS (group 1, n=14) were compared with patients with AIS changes (group 2, n=7), and t test and χ test were performed (p<0.05). - RESULTS: Differences in both groups concerning fracture classification were confirmed (p=0.046). A relation between neurologic improvement in the AIS and the severity of trauma (p=0.058) after 1 year was not found. The subitem PTST in the thoracic area showed statistical significance comparing the two groups (p=0.005). Both groups significantly improved functionally (Spinal Cord Independence Measure, p=0.035) during the first year but with no significant difference between the groups after 1 year. - CONCLUSIONS: Our data suggest that functional improvement is achieved independently from neurologic recovery. The combined assessment of the PTS, the AO classification, and the AIS in multiple-injured paraplegic patients can contribute to provide a better prognostication of the neurologic changes during rehabilitation and the outcome after 1 year than the AIS alone.
Gesehen am 20.01.2023